The Role of Consumer Satisfaction in Mediating the Effect of Service Quality and Price Discount Framing on Hypermart Consumer Loyalty in the Province of Central Kalimantan, Indonesia - Meitiana; Kristinae, Vivy; Telaumbanua, Astuti (Archives of Business Research, 2022)
Research in the field of marketing management aims to increase consumer loyalty by mediating consumer satisfaction, on the influence of service quality and price discount framing on consumer loyalty, either directly or indirectly, where customer satisfaction is an intervening variable. The research method used in this research is an associative-quantitative research approach. The population and sample in this study were customers or people who had shopped at a large supermarket Hypermart in Palangka Raya City in Indonesia. The number of research respondents was 105 hypermart customers. The results show that service quality has a positive and significant effect on consumer satisfaction, service quality has a positive and significant effect on consumer loyalty, price discount framing has a negative and insignificant effect on consumer satisfaction, price discount framing has a positive and significant effect on consumer loyalty, and consumer satisfaction has an effect on positive and significant impact on consumer loyalty, service quality has a positive and significant effect on consumer loyalty through customer satisfaction, and price discount framing has a positive and significant effect on consumer loyalty through customer satisfaction. The novelty of the price discount framing variable in increasing consumer loyalty, for further research can include the value innovation variable.